A Nonisolated High Gain DC – DC Converter with Two Inductor Structure for EV Applications - Aravind R; Bharatiraja C (Journal of Applied Science and Engineering)
The electric vehicle (EV) system is increasingly recognized for its capacity to integrate renewable energy sources such as photovoltaic cells, batteries, and fuel cells. However, one major challenge lies in the low output voltage produced by these energy sources, which requires the use of high-performance DC-DC converters for effective application in EV systems. Existing converters often struggle to achieve the necessary voltage gain without imposing significant stress on components or sacrificing efficiency. This paper addresses these issues by proposing a novel non-isolated DC-DC converter specifically designed to achieve high voltage gain while maintaining flexibility through a variable switch ratio. This design eliminates the need for additional boost cells to reach higher voltage levels. This work also focuses on reducing component stress and improving overall operational efficiency, key factors for the reliability and longevity of EV systems. The primary contribution of this converter topology, is to validated through simulation results from a 1 kW system, achieving an output voltage of 230V. The proposed converter demonstrates its potential in enhancing energy management and improving efficiency in electric vehicles, offering a promising solution for future advancements in EV technology.